2017
DOI: 10.2991/itmr.2017.6.3.4
|View full text |Cite
|
Sign up to set email alerts
|

User adoption of mobile commerce in Bangladesh: Integrating perceived risk, perceived cost and personal awareness with TAM

Abstract: This paper develops and tests a model for predicting user adoption of mobile commerce (i.e. e-commerce using mobile phones) in developing countries. The model takes up the Technology Acceptance Model (TAM) determinants of perceived usefulness and perceived ease of use, and extends these through the inclusion of three further determinants: perceived risk, perceived cost and personal awareness to enable prediction of the likelihood of mobile commerce adoption by users in the developing world. 575 usable surveys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 28 publications
4
27
0
Order By: Relevance
“…Consistent with prior research [6,63], findings confirm a significant and negative association (p < 0.01) between perceived risks and perceived usefulness (H3). This result reflects the health professionals' concern about privacy and confidentiality, the main items that represent the construct of perceived risk in the healthcare context.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with prior research [6,63], findings confirm a significant and negative association (p < 0.01) between perceived risks and perceived usefulness (H3). This result reflects the health professionals' concern about privacy and confidentiality, the main items that represent the construct of perceived risk in the healthcare context.…”
Section: Discussionsupporting
confidence: 88%
“…There are six components of perceived risk and they are as follows: (i) financial, (ii) performance, (iii) social, (iv) physical, (v) privacy, and (vi) time loss [60]. Prior studies have consistently shown that perceived risk negatively influences users' intention to use IT/IS systems [61][62][63].…”
Section: Perceived Riskmentioning
confidence: 99%
“…Besides, Mohammadi (2015) found that the mobile banking system's PU and efficiency positively affect Iranian mobile banking users' attitudes. Previous studies have revealed that customers in the developing economy like Bangladesh seek convenience in their technological usages, and PU is a predominantly crucial predictor of user attitude and mcommerce adoption (Islam et als, 2011;Rahman and Sloan, 2017). In particular, in the era of the corona pandemic, where contactless payment is required for safety, MFS providers in Bangladesh have experienced a boost due to a greater degree of PU and positive attitude (Kabir, 2020).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The high initial cost, which is associated with any new technology, product, or service, is often seen as a major obstacle towards their acceptance [54], [55]. A number of previous studies on innovative and new services ranging from mobile-commerce systems, e-training services, high-speed home-based broadband access to the acceptance of smartmeters have found a close relationship between cost and user perception [56]- [59]. Generally, the elderly people lead a retired life, and therefore have a limited source of income.…”
Section: E Service Cost (Sc) (Service-specific Characteristics)mentioning
confidence: 99%